Symmetric dimethylarginine, high-density lipoproteins, and cardiovascular risk assessment: are we ready for clinical use? - Mangoni, Arduino A.; Zinellu, Angelo; Sotgia, Salvatore; Carru, Ciriaco (Journal of Laboratory and Precision Medicine, 2017)
There is very good evidence that patients with chronic kidney disease (CKD), particularly those with end-stage renal disease (ESRD), have an increased risk of cardiovascular morbidity and mortality when compared with the general population (1).